2016
DOI: 10.3357/amhp.4391.2016
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Comparison of Color Vision Tests for Military Screening

Abstract: The current U.S. Army CV screening tests demonstrated good sensitivity and specificity, as did the automated tests. In addition, some current PIP tests (Dvorine, PIPC), and the CCT performed no worse statistically than the anomaloscope with regard to sensitivity/specificity. The CCT letter presentation is randomized and results would not be confounded by potential memorization, or fading, of book plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Military screenings using CCT demonstrate 96-100% sensitivity and specificity for protan, deutan, and tritan CVD compared to the anomaloscope. 1,11 Our study team has also demonstrated in data under review that there was no learning effect, or improvement in scores, when individuals repeated this test multiple times 12…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Military screenings using CCT demonstrate 96-100% sensitivity and specificity for protan, deutan, and tritan CVD compared to the anomaloscope. 1,11 Our study team has also demonstrated in data under review that there was no learning effect, or improvement in scores, when individuals repeated this test multiple times 12…”
Section: Introductionmentioning
confidence: 90%
“…Human trichromatic vision enables the detection of 2.3 million colors with discrimination between wavelength differences of as little as 0.25 nm. 1 Despite 50 percent of visual information originating from color-sensitive cones in the fovea, clinical visual function testing is largely limited to visual acuity (VA) which quantifies minimal angle of resolution under maximal contrast (black-on-white) conditions. With its ease of use and wide accessibility, VA is the most used visual function test and is the “gold standard” for retinal disease clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth type of tests are spectral tests, based on anomaloscopes: the subject is asked to realize metameric matches of a target coloured light spot (for instance yellow light) by mixing two monochromatic lights (for instance red and green light). Although very precise, this later type of test use is restricted to scientific research [8], be-cause of the high cost and need for extensive training of examiner.…”
Section: Colour Blindness Assessment Testsmentioning
confidence: 99%